Lazaroid U-74389G Administration in Pancreatic Ischemia-Reperfusion Injury: A Swine Model Encompassing Ischemic Preconditioning - Chrysikos, Dimosthenis T; Sergentanis, Theodoros N; Zagouri, Flora; Psaltopoulou, Theodora; Theodoropoulos, George; Flessas, Ioannis; Agrogiannis, George; Alexakis, Nikolaos; Lymperi, Maria; Katsarou, Ageliki I; et al. (JOP. Journal of the Pancreas, 2015)
Context The potential of lazaroid U-74389G in attenuating injury after ischemia and reperfusion has been reported in various organs. Objective The present study focuses specifically on the pancreas and aims to examine any effects of U-74389G in a swine model of pancreatic ischemia and reperfusion, encompassing ischemic preconditioning. Methods Twelve pigs, weighing 28–35 kg, were randomized into two experimental groups. Group A (control group, n=6): Two periods of ischemic preconditioning (5 min each) separated by a 5-min rest interval; then ischemia time 30 min and reperfusion for 120 min. Group B (n=6): the same as above, with U-74389G intravenous injection in the inferior vena cava immediately prior to the initiation of reperfusion. Blood sampling and pancreatic biopsies were conducted at 0, 30, 60, 90 and 120 min after reperfusion. Results Repeated-measures ANOVA was undertaken to evaluate differences between the two study groups. No statistically significant differences were noted concerning the histopathological parameters in the control and therapy groups (P=0.563 for edema, P=0.241 for hemorrhage, P=0.256 for leukocyte infiltration, P=0.231 for acinar necrosis and P=0.438 for vacuolization). In accordance with the above, serum metabolic data (glucose, creatinine, urea, total and direct bilirubin, total calcium, amylase, lipase, SGOT/AST, SGPT/ALT, ALP, GGT, LDH, CRP, insulin) were not significantly different between the two groups; similarly, tumor necrosis factor-α values (P=0.705) and tissue malondialdehyde levels (P=0.628) did not differ between the two groups. Conclusion This swine model of pancreatic ischemia and reperfusion, encompassing preconditioning, indicates that U-74389G lazaroid does not seem to exert protective effects from pancreatic damage. Image: Complete distortion of the pancreatic parenchyma (H&E x400).